Efforts to Realize Sustainable Coastal Development Through Integrated Coastal Tourism Management - Kismartini, Kismartini; Warsono, Hardi; Afrizal, Teuku (Iapa Proceedings Conference, 2024)
One of the causes of the threat to the sustainability of coastal ecosystems is environmental pressure resulting from tourism industry activities. The purpose of this study is to analyze how to realize sustainable coastal areas through integrated tourism management with the consideration that tourism is not only a business activity that generates income for business units but also as a tool to balance the benefits of development and conservation of natural and cultural resources. The Integrated Coastal Tourism Management approach is used as the basis for this study, by analyzing 4 integrations, namely regional integration, sector integration, integration of scientific disciplines and stakeholder integration. This study uses qualitative research methods, with data collection techniques through in-depth interviews, FGDs, observations and document studies. The results of the study indicate that tourism management has attempted to manage coastal tourism in an integrated manner through: 1) Regional integration is realized in cooperation between regions; 2) Sector integration is realized in cooperation between agencies; 3) Integration of scientific disciplines is realized in the form of regulations and the formation of special bodies; 4) Stakeholder integration is realized in the form of routine meetings that are accommodated in special bodies. Although integrated coastal management has been developed, the achievement for sustainable coastal development is not yet optimal, there is still some damage to coastal ecosystems. Therefore, it is necessary to improve coordination between sectors to realize a sustainable coast.